2000
DOI: 10.1590/s0100-879x2000000300007
|View full text |Cite
|
Sign up to set email alerts
|

HFE gene mutations in coronary atherothrombotic disease

Abstract: Although iron can catalyze the production of free radicals involved in LDL lipid peroxidation, the contribution of iron overload to atherosclerosis remains controversial. The description of two mutations in the HFE gene (Cys282Tyr and His63Asp) related to hereditary hemochromatosis provides an opportunity to address the question of the association between iron overload and atherosclerosis. We investigated the prevalence of HFE mutations in 160 survivors of myocardial infarction with angiographically demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 27 publications
3
20
1
2
Order By: Relevance
“…The frequencies of C282Y and H63D mutations found in this study are greater than those reported for the general Brazilian population, 1,8,11,13,15,[17][18][19][20][21][22] but are smaller than the genotypic frequencies among patients with HH. 2,3,4 It is unquestionable that C282Y is the main mutation responsible for HH in all studied populations, as the majority of published reports worldwide cite its prevalence in more than 80% of individuals with clinical manifestations of HH, 1,[4][5][6]12,15,17,23 thus several other diagnostic guides are based on the result of C282Y mutation genic testing.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…The frequencies of C282Y and H63D mutations found in this study are greater than those reported for the general Brazilian population, 1,8,11,13,15,[17][18][19][20][21][22] but are smaller than the genotypic frequencies among patients with HH. 2,3,4 It is unquestionable that C282Y is the main mutation responsible for HH in all studied populations, as the majority of published reports worldwide cite its prevalence in more than 80% of individuals with clinical manifestations of HH, 1,[4][5][6]12,15,17,23 thus several other diagnostic guides are based on the result of C282Y mutation genic testing.…”
Section: Discussioncontrasting
confidence: 84%
“…3 In the present study, the allele frequency of H63D was 0.196 and in accordance with the majority of the other world populations, in which the frequency ranges from 0.1 to 0.2; it is important to note that Spain and Portugal, countries that greatly influenced colonization of Brazil, present frequencies greater than 0.2 in their general populations. 4,11 The frequency of 0.03 for C282Y/H63D compound heterozygotes is in accordance with data already reported for the American population, 14 but it does not concur with Brazilian data, 1,11,15,21,22 probably because of the quantitative difference of the studied populations and because of the fact that this paper assessed individuals with clinical suspicion of HH. Thus, this frequency values the role of the C282Y/ H63D genotype in the development of HH.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…9,16 Os estudos brasileiros publicados estimam que a prevalência da mutação C282Y é cerca de três a oito vezes menor comparada à observada nos indivíduos caucasianos do nordeste europeu, enquanto a freqüência das mutações H63D e S65C é semelhante entre estas populações. [17][18][19][20][21] Entretanto, não encontramos nenhum trabalho que tenha analisado os efeitos do genótipo HFE sobre o estado de ferro do organismo e a influência de fatores genéticos, clíni-cos ou ambientais nos doentes com mutação do gene HFE.…”
Section: Introductionunclassified